Diabetic painful polyneuropathy treatment - Terzić Branka (Serbian Journal of Anesthesia and Intensive Therapy, 2017)
Diabetic peripheral neuropathies (DPN) are a heterogeneous group of disorders caused by neuronal dysfunction in patients with diabetes. Among all acquired polyneuropathy, diabetic polyneuropathy is the most common, and therefore the most important one. Approximately 50% of patients with diabetes develop peripheral neuropathy. Distal symmetrical polyneuropathy (DSPN) with painful diabetic neuropathy, occurring in around 20% of diabetes patients, and diabetic autonomic neuropathy (DAN) are the most common manifestations of DPN. Optimal glucose control represents the only broad- ly accepted therapeutic option though evidence. A number of symptomatic treatments are recommended in clinical guidelines for the management of painful DPN, including antidepressants, γ-aminobutyric acid analogues, opioids, and topical agents. The current treatment of DPN is largely symptomatic, the other therapy direction is focused on pathogenetic process of disease, and there is some evidence that the use of alfa-lipoic acid, aldose reductase inhibitors and fat-solubile vitamin-B may have beneficial effect in terms of development of microangiopathy in patients with diabetes.